Activity patterns and use of artificial water ponds by White-tailed deer (Odocoileus virginianus) in western Campeche - Hidalgo-Mihart, Mircea G; Jesús-de la Cruz, Alejandro; Bravata-de la Cruz, Yaribeth; Contreras-Moreno, Fernando M. (THERYA, 2024)
Artificial Water Ponds (AWP) are widely employed for preserving and managing white-tailed deer (Odocoileus virginianus) in arid, and tropical regions of Mexico. However, there is a significant knowledge gap concerning the impact of these AWP on white-tailed deer activity. To determine the effect of AWP on the ecological aspects of white-tailed deer, we assessed the visitation rates and activity patterns of this species in AWP and compared them with areas devoid of water such as Dirt Roads (DR) using camera traps during the dry season within the seasonal wetland region of Nicte Ha, situated in western Campeche, Mexico. The research was conducted in a highly seasonal tropical wetland area at the Nicte-Ha UMA in southwestern Campeche, México. We established set camera trap stations during the dry season of 2019, 2020, and 2021 in seven AWP and 12 DR that operated for at least 80 days and compared the white-tailed deer visitation rate (measured as the Relative Abundance Index, RAI) and activity patterns among both treatments and across the three studied years. We collected a total of 3,640 independent records of white-tailed deer (2,584 in AWP and 1,056 in DR) for three years, with a combined effort of 3,978 camera days (1,306 camera days in AWP and 2,672 in DR). Our analysis revealed that the Relative Abundance Index (RAI) was consistently higher in the AWP than the DR across the three study years. However, we examined RAI variations over the three years and observed differences in the AWP, while the DR exhibited a relatively stable pattern. In the case of the activity patterns, we observed that white-tailed deer were primarily diurnal, with a significant overlap in activity between the two treatment areas. Nonetheless, within the AWP, the species exhibited continuous daytime activity, whereas, in the PR, distinct activity peaks occurred during sunrise and sunset. The results show that the presence of AWP in Nicte Ha has important effects on the presence of white-tailed deer during the dry season since we observed that there is a higher RAI in the sites where there is AWP compared to the PR sites. In the case of activity patterns, the AWP sites maintain constant activity throughout the day compared to DR, where activity peaks associated with sunrise and sunset occur. Our results show the importance that this type of structure has for the management of the species during the dry season of the year in Nicte Ha and the potential benefits of these structures in tropical seasonal areas, especially under a scenario in which drought during the dry season may be more severe in the near future due to the global change.